Antithrombotic potency of ticagrelor versus clopidogrel in type-2 diabetic patients with cardiovascular disease - Zafar, M. Urooj; Baber, Usman; Smith, Donald A.; Sartori, Samantha; Contreras, Johanna; Rey-Mendoza, Juan; Linares-Koloffon, Carlos A.; Escolar, Gines; Mehran, Roxana; Fuster, Valentin; Badimon, Juan J. (Thrombosis and Haemostasis, 2017)
Type-2 Diabetes Mellitus [T2DM] is associated with increased platelet reactivity and hypo-response to antiplatelet drugs. Ticagrelor, with its faster and more potent antiplatelet effects, was shown to reduce adverse events more than clopidogrel in the overall CAD patient population of PLATO trial, but the benefits did not reach statistical significance in the T2DM subgroup. To better understand these findings, we compared the antithrombotic effects of ticagrelor versus with clopidogrel in T2DM patients with cardiovascular disease. In a randomized, 2 treatment-sequence, crossover-design, T2DM patients (n=20, 57±8 years, 60% male) received a loading-dose [LD] plus one week of daily-therapy [DT] of clopidogrel or ticagrelor. Treatment effects were assessed by measuring thrombus formation (Badimon Chamber) and platelet aggregation (Multiple Electrode Aggregometry (MEA) Analyzer and VerifyNow®) at 2- and 6-hour post-LD and on Day-7 of DT, in comparison with pre-treatment baseline. After 2 weeks of washout, patients switched to the second treatment under identical testing conditions. Ticagrelor significantly reduced thrombus formation versus baseline at 2- and 6-hour post-LD and Day-7 of DT (33%, 40% and 31%, respectively, p<0.01 for all) whereas thrombus reductions with clopidogrel were much lower and significant only at 6-hour post-LD (16%, 20% and 17%, respectively). Antithrombotic effect of ticagrelor at 6-hour was significantly stronger than clopidogrel (p<0.05). Platelet aggregation (MEA and VerifyNow®) was inhibited by both treatments but effects of ticagrelor were significantly stronger at each time-point. Ticagrelor exhibits a faster and more potent antithrombotic effect than clopidogrel in T2DM patients with cardiovascular disease, supporting its use in this population.Clinical Trial Registration: Unique Identifier: NCT01823510.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Antiplatelet agents; clopidogrel; diabetes mellitus; thrombosis; ticagrelor